Pengaruh Lingkungan Kerja Fisik dan Disiplin Kerja terhadap Kinerja Karyawan pada Solo Swalayan di Kabupaten Berau - Dicky Setiawan (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Physical work environment and work discipline are important to improve performance. managing the physical work environment is to create optimal conditions for employees to work comfortably, efficiently and productively, while the application of work discipline in the organization is to create a structured and productive work environment by ensuring that all employees comply with the policies, procedures and standards set by has been set. This research examines the influence of the physical work environment, work discipline, and employee performance at Solo Swalayan. The physical work environment includes factors such as work space comfort, lighting, ventilation, and ergonomics, while work discipline includes compliance with policies, rules, and procedures established by the company. Using quantitative methods, Multiple Linear Regression statistical data with Solo Swalayan employees as research objects. This research evaluates how these two variables affect overall employee performance. Based on the research results, it shows that the physical work environment and work discipline partially have a significant effect on employee performance. As well as the research results, physical work environment variables and work discipline simultaneously have a significant effect on the performance of Solo Swalayan employees.